A new genus and species of the family Anthroleucosomatidae from Serbia (Myriapoda, Diplopoda, Chordeumatida) - Makarov S.E.; Ćurčić B.P.M.; Milinčić M.; Pecelj Milica M.; Antić D.; Mitić B.M. (Archives of Biological Sciences, 2012)
A new genus and species of Anthroleucosomatidae is described from Serbia. Dazbogosoma naissi n. g. n. sp. is characterized by the presence of few ocellae, apically bifurcated syncoxite, and the presence of complex lateral parts of anterior gonopods with truncated process. The new genus belongs to the Bulgarosoma complex of genera that probably deserve a suprageneric level.